A Case Report of Supplement-Induced Hepatitis in an Active Duty Service Member. Issue 7 (1st July 2015) - Brazeau, Michael J.; Castaneda, Joni L.; Huitron, Sonny S.; Wang, James
ABSTRACT: The incidence of drug-induced hepatic injury has been increasing as a result of more widespread use of workout supplements containing anabolic steroids to increase muscle mass. Synthetic androgenic steroids are shown to cause cholestatic liver injury, but the exact mechanism of injury is not completely understood. We present a case of a healthy, young, active duty Army male soldier who developed pruritis and jaundice shortly after starting to take a body-building supplement containing anabolic steroids, and was subsequently found to have significant biopsy proven drug-induced liver injury.